PROSES PEMBUKTIAN JUMLAH KERUGIAN NEGARA AKIBAT TINDAK PIDANA KORUPSI DI PENGADILAN NEGERI PADANG (Studi Kasus Pada Pengadilan Tipikor Di Pengadilan Negeri Padang) - Supran Supran (Ensiklopedia Social Review, 2019)
Process verification of state quantity costs due to corruption regulated in law number 8 of 1981 on the Criminal Procedure Law. The verification of state quantity costs arising from of corruption is difficult to find. This cause by several factors. The problems in this research is: (1) how the process verification of state quantity costs from corruption? (2) what is obstacles find from officials in the process of proving total losses of countries on criminal acts of corruption ?(3) how correlation due to the number of the state a loss of corruption in drop by a judge? This research adopting juridical sociological, the data use covering primary and secondary data. Data is collect through interviews , the study documents and analyzing with qualitatively .The results of research it: (1) the process of due to the number of the state a loss of corruption in a total loss. (2) the obstacles find in the process of proving for of public prosecutors and judges namely covering juridical obstacles and non juridical? (3) Correlation amount of losses that the State decide by the judge as a criminal judgment in the case of restitution for the losses that State.